The Effect of Ownership Structure, Financial and Environmental Performances on Environmental Disclosure - Dintimala, Yossi; Amril, Tri Amalia (Universitas Negeri Semarang, 2018)
This study aims to examine the effect of ownership structure, financial performance, firm size, industrial sector, and environmental performance on corporate environmental disclosure. The sample is the companies participating in PROPER period 2010 – 2014 which are listed in Indonesian Stock Exchange. Participants of PROPER are companies that are vulnerable to the environmental damage. The sample must a company that publishes the financial statement in rupiah and the environmental disclosure. There are 53 PROPER companies listing in Indonesian Stock Exchange period 2010 – 2014. It is only 30 of 53 companies publish their financial statement in rupiah and publish environmental disclosure every year. The final observation is 150 firms – years. The result indicates that firms will publish environmental disclosure when managerial ownership lower, institutional ownership lower, and financial performance lower, total assets higher, firms with higher environmental compliance according to PROPER, firms in manufacturing and mining sectors of oil and gas (PEM), and the score of environmental performance higher. The results are consistent with all hypotheses.